Comanagement and reconciling of ecological and economic benefits in an Amazonian freshwater fishery - Monalisa R. O. Silva; Leandro Castello; Carolina T. Freitas; João V. Campos‐Silva; Carlos A. Peres; Evlyn M. L. M. Novo (Conservation Biology, 2025)
Freshwater ecosystems contribute substantially to the global fish catch. However, freshwater fisheries face growing human pressures and are underrepresented in global analyses and conservation strategies. Attempts to reconcile conservation and human welfare goals in fisheries have led to comanagement by the government and local communities, along with other stakeholders, but assessments of its effectiveness in freshwater fisheries are lacking. We investigated the effectiveness of comanagement in freshwater fisheries by assessing ecological (fish catch) and economic (fishing revenue) outcomes in a major tributary of the Amazon Basin. Fisheries comanagement in the Amazon is typically implemented through an approach developed by riverine communities called lake management in which floodplain lakes are categorized as open access, subsistence, or protected. Each category has different levels and types of fishing pressure. We analyzed data (e.g., fishing data and management rules) from 1607 fishing trips of 198 fishers over 5 years in 30 riverine communities in 74 floodplain lakes (20 open access, 33 subsistence, and 21 protected). Lake comanagement increased fish catch in protected lakes over time by 12% (2.4 kg) compared with subsistence lakes and by 13% (2.6 kg) compared with open‐access lakes ( p = 0.03). Increased fish catch in protected lakes was mainly due to limits on fishing effort. Fishing revenue was 63% greater in protected lakes than in open‐access lakes ( p